LEGAL REVIEW OF MURDER THROUGH 'SANTET' IN THE LEGAL PERSPECTIVE OF INDONESIA (A STUDY OF LAW NO. 1 OF 2023 REGARDING 'SANTET') - Gunawan Nachrawi; Sukamto Kusnadi (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2023)
: